Responding to human trafficking among refugees: prevalence and test accuracy of a modified version of the adult human trafficking screening tool - Tambini Stollwerck, Estella; Dönnhoff, Ivo; Friederich, Hans-Christoph; Nikendei, Christoph (BMC public health, 2024)
Background: Human trafficking is a human rights violation and urgent public health challenge. It involves the exploitation of a person by means of force, intimidation or deceit and causes severe health risks. Though it occurs all over the world, its true extent is still unknown. Refugees are especially vulnerable to human trafficking due to language barriers and difficult living conditions. Therefore, the purpose of this study was to estimate the prevalence and design a screening tool to identify survivors of all forms of human trafficking among refugees in a German state registration and reception centre. Methods: In cooperation with the local authorities and the Ministry of Justice and for Migration Baden-Württemberg, we interviewed newly arrived refugees at an initial reception centre in Southern Germany to assess the prevalence of human trafficking. We used both a combination of the Adult Human Trafficking Screening Tool and a publication by Mumma et al. to assess all forms of human trafficking. Results: In total, 13 of the 176 refugees had experienced trafficking, which corresponded to a prevalence of 7.3% (95%-CI = [3.5%, 11.3%]). Across all languages the questionnaire had a sensitivity of 76.9% and a specificity of 84.0% at a recommended cut-off of six positive responses. The recommended cut-off differed slightly for the Arabic, Farsi, Turkish, and English version. In an exploratory descriptive analysis on subregions, refugees from West Africa had a substantially higher prevalence (33.3%, 8 out of 24) for human trafficking within our sample, especially women. However, when we excluded this region from our analysis, we found no significant gender difference for the rest of the sample. Conclusions: The high prevalence of trafficking in most regions, regardless of gender, suggests that more effort is needed to identify and protect all trafficked persons. The designed screening tool seems to be a promising tool to detect an especially vulnerable group of refugees and provides assistance in identifying survivors of human trafficking.
Gesehen am 06.12.2024